EVALUASI PEMBELAJARAN PENDIDIKAN JASMANI PADA MASA PANDEMI COVID-19 DI SMP NEGERI SE-KOTA PONTIANAK - Tio, Seprianus; Simanjuntak, Victor G; Hidasari, Fitriana Puspa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
The problem in this study is how to apply the evaluation of physical education learning during the COVID-19 pandemic mass which was carried out online by teachers at SMPNs throughout the city of Pontianak. This study aims to determine the mechanism for assessing student learning outcomes during the COVID-19 pandemic. The research method used is quantitative descriptive, the sample of this research is the teachers of Physical Education, Sports and Health. In this study using a questionnaire on google form about summative and formative assessments by teachers of Physical Education, Sports and Health. The results of this study indicate that 49% of teachers stated that they could assess the learning progress of students, while 51% of teachers stated that they could not assess the learning progress of students in online learning.